Implementasi Pengadaaan Sarana Dan Prasarana Pendidikan Madrasah Dengan SIM-SARPRAS - Putri, Nabila Jovani; Antariksa, Walid Fajar (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
Management of procurement of facilities and infrastructure is very important in supporting the smooth implementation of teaching and learning activities to be effective and efficient for each educational institution unit. The Ministry of Religion of the Republic of Indonesia has created the Madrasah Infrastructure Information System (SIM-SARPRAS) application to regulate the management of submission of assistance for facilities and infrastructure submitted by all madrasas or educational institutions in Indonesia. This study aims to analyze the implementation of SIM-SARPRAS procurement of facilities and infrastructure. This study uses a qualitative approach with field research type. The research data was obtained from the results of interviews, observations and documentation. The results of this study are that the process of submitting assistance for procurement of facilities and infrastructure with the SIM-SARPRAS application has used the established Standard Operating Procedure (SOP). The process begins with schools submitting proposals for requests for school facilities and infrastructure which are entered through the SIM-SARPRAS application, then the Batu City Ministry of Religion Office will check and provide recommendations to the madrasah to be forwarded to the East Java Provincial Ministry of Religion Regional Office which will then forward it to the Ministry of Religion. Once approved, the madrasah will receive a budget that will be sent directly to the account to be used in procurement. After the procurement is complete, the madrasah will make an accountability report. This SIM-SARPAS application makes the process of submitting procurement of facilities and infrastructure from madrasahs to the government faster and more practical compared to the previous manual process, which took longer. However, there are still things that need to be improved, such as the long submission stages that take a long time, and the difficulty of monitoring whether the submission status has been verified or approved, because this can only be known by the central operator.